On the role of Ag in enhanced age hardening kinetics of Mg–Gd–Ag–Zr alloys. (2nd June 2016) - Zhang, Yu; Alam, Talukder; Gwalani, Bharat; Rong, Wei; Banerjee, Rajarshi; Peng, Li-Ming; Nie, Jian-Feng; Birbilis, Nick
Abstract: The addition of Ag to the age hardenable Mg–Gd–Zr alloy system dramatically enhances early stage age hardening kinetics. Using atom probe tomography (APT), Ag-rich clusters were detected in a Ag-containing Mg–Gd–Zr alloy immediately after solution treatment and water quenching. During subsequent isothermal ageing at 200 °C, a high density of basal precipitates was observed during the early stages of ageing. These basal precipitates were enriched with Ag and Gd, as confirmed by APT. It is posited that Ag-rich clusters in the context of quenched-in vacancies can attract Gd atoms, increasing diffusion kinetics to facilitate the formation of the Ag + Gd-rich basal precipitates. The rapid formation of Ag + Gd-rich precipitates was responsible for accelerated ageing.